Epidemiological analysis of injuries in elite handball: insights from the 2023-2024 Turkish super league season - Bayrak, A.; Enli, M. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background This study aims to determine the injury incidence among male and female athletes in the Turkish Handball Super League and to examine the most common types, mechanisms, and risk factors of injuries.